Inactivation of Phaeodactylum tricornutum urease gene using transcription activator‐like effector nuclease‐based targeted mutagenesis. Issue 4 (10th October 2014) - Weyman, Philip D.; Beeri, Karen; Lefebvre, Stephane C.; Rivera, Josefa; McCarthy, James K.; Heuberger, Adam L.; Peers, Graham; Allen, Andrew E.; Dupont, Christopher L.
Summary: Diatoms are unicellular photosynthetic algae with promise for green production of fuels and other chemicals. Recent genome‐editing techniques have greatly improved the potential of many eukaryotic genetic systems, including diatoms, to enable knowledge‐based studies and bioengineering. Using a new technique, transcription activator‐like effector nucleases (TALENs), the gene encoding the urease enzyme in the model diatom, Phaeodactylum tricornutum, was targeted for interruption. The knockout cassette was identified within the urease gene by PCR and Southern blot analyses of genomic DNA. The lack of urease protein was confirmed by Western blot analyses in mutant cell lines that were unable to grow on urea as the sole nitrogen source. Untargeted metabolomic analysis revealed a build‐up of urea, arginine and ornithine in the urease knockout lines. All three intermediate metabolites are upstream of the urease reaction within the urea cycle, suggesting a disruption of the cycle despite urea production. Numerous high carbon metabolites were enriched in the mutant, implying a breakdown of cellular C and N repartitioning. The presented method improves the molecular toolkit for diatoms and clarifies the role of urease in the urea cycle.